Aproximación Al Estudio De La Prensa Durante La Segunda República - Barreiro, Cristina (Re-presentaciones: Periodismo, comunicación y sociedad, 2007)
This Article analizes the situation of Spanish Press during the so-called "Second Republic" (1931-1936), starting from a legal context that stablished an atmosphere of freedom based on december constitucion. Some laws that were used to hasten constitutional regimen then have also been analyzed here, has the role of politized Madrid Press in front of the political turmoil that then affected Spain, and how Goverment administration from one other biennial used legal frame to make their interests prevail.
Keywords: Republic; Constitution Chart; Censorship; Public Order